The enabling factors for green building development in housing projects / Nur Atifah Bahruddin and Thuraiya Mohd - Bahruddin, Nur Atifah; Mohd, Thuraiya (2018)
Transformation of the housing industry in Malaysia deliver tremendous benefits but it requires a lot of involvement and efforts from various parties to implement. Here, the transformation of green housing is able to preserve natural environment by fulfilling the quality of lifestyle of homeowners. Green housing designed sustainable resources with maximizing the resources and produces less impact on the environment. In other words, green housing is designed to reduce environmental impacts in suitable manners to meet the present without compromising the current needs of future generations as intended to enhance environmental friendly and sustainable development. Currently, green housing has received significant attention in Malaysia over the years with significant growth in environmental awareness. Furthermore, the Malaysian government had shown interest and encourages the practice of green development by introducing green building index (GBI) as green rating tool for buildings to promote sustainability and growing awareness among construction players. However, the implementation of green housing is quite low-moderate due to facing barriers to be implemented. Thus, this research put emphasis on determination of the significant enabling factors considered in developing green housing projects. The research presents data collected through questionnaire survey conducted to the developers as respondents. The data were analyzed through the quantitative method by using Confirmatory Factor Analysis (CFA) technique. The finding shows the main enabling factors for developing green housing projects are institutional, knowledge, internal action and market influence. As a result, this research is attempted to highlight the significant enabling factors being considered by developers in developing green housing projects